Higher education aspirations and barriers among Malaysian students from low-income families: development of a conceptual framework - Abdullah, Arnida (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Most developing countries have realized the importance of education for upward social mobility and economic growth. An individual’s social status can change from one social class to another as higher education brings higher wages, better job prospects and quality of life. The decision to pursue further education after finishing secondary schools, however, requires consideration of many choices as there are thousands of higher institutions from which to choose. Economic (monetary) and individual, social and culture factors are more likely to influence the decision-making process. This includes the weight they give to economic and social benefits of attending college, the material constraints they experience (e.g., fees, travel) in view of their socio-economic backgrounds, and assessment of their academic ability and academic record. One or more of these factors may hinder their aspirations for higher education. This paper, therefore, aimed at identifying barriers inhibiting higher education aspirations among students from low-income families. The findings from literature review were then used to illustrate a proposed conceptual framework that shows several barriers to higher educational aspirations faced by students from low-income families in Malaysia.